O aktywności społeczno-ekonomicznej kobiet w czasopiśmie „Twój Styl” - Kozłowska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
The text is about the issue theme of socio-economic activity of women in the text analyzes the issue theme of socio-economic activity of women in the Polish magazine “Twój Styl”. The analysis leads to the conclusion that the image of modern woman is a bit fuzzy. Typical woman is torn between the private and public sphere and forced (through social practices and effective gender stereotypes) into an attempt at the collision-free fulfillment of the social roles. The prevailing stereotype that woman are limited to the private sphere is the one of the causes of female disadvantage on the labor market. At the same time that stereotype creates an impression that woman in the public sphere is a rarity and if she’s ever managed to enter it, it was only possible thanks to the support of her male partner or by limiting her personal life.